Preparation and characterization of superfine ammonium perchlorate (AP) crystals through ceramic membrane anti-solvent crystallization - Ma, Zhenye; Li, Cheng; Wu, Rujun; Chen, Rizhi; Gu, Zhenggui (Journal of crystal growth, 2009)
In this paper, a novel ceramic membrane anti-solvent crystallization (CMASC) method was proposed for the safe and rapid preparation ammonium perchlorate (AP) crystals, in which the acetone and ethyl acetate were chosen as solvent and anti-solvent, respectively. Comparing with the conventional liquid anti-solvent crystallization (LASC), CMASC which successfully introduces ceramic membrane with regular pore structure to the LASC as feeding medium, is favorable to control the rate of feeding rate and, therefore, to obtain size and morphology controllable AP. Several kinds of micro-sized AP particles with different morphology were obtained including polyhedral-like, quadrate-like to rod-like. The effect of processing parameters on the crystal size and shape of AP crystals such as volume ratio of anti-solvent to solvent, feeding pressure and crystallization temperature were investigated. It is found that higher volume ratio of anti-solvent to solvent, higher feeding pressure and higher temperature result in smaller particle size. Scaning electron microscopy (SEM) and X-ray diffraction (XRD) were used to characterize the resulting AP crystals. The nucleation and growth kinetic of the resulting AP crystals were also discussed.